Impact of corporate governance on disclosure quality: empirical evidence from listed banks in Malaysia - Htay, Sheila Nu Nu; Said, Ridzwana; Salman, Syed Ahmed (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
The Asian financial crisis in 1997 has awakened the regulators and corporates on the importance of corporate governance. In any country’s economy, banking sector plays an important role for the better economy. Accordingly, the objective of this study is to examine the relationship between corporate governance and disclosure quality of listed banks on Bursa Malaysia. Corporate governance variables tested in this study are the board leadership structure, board composition, board size, director ownership, institutional ownership and block ownership. The researchers developed the disclosure index and it will be checked against the information disclosed in the annual reports. Then, in calculating the weighted disclosure score, the views of accountants and financial analysts are also considered through survey questionnaire. The results reveal that better disclosure quality of the annual reports in banking sector can be achieved by having separate board leadership structure, higher proportion of independent non-executive directors, higher board size, lower ownership by the directors, institutional and block shareholders.